Le rôle des riverains dans le façonnement des interfaces ville-forêt - Christine Bouisset; Isabelle Degrémont (Projets de Paysage)
The aim of this article is to analyse the ways in which resident populations inhabit suburban plots of land on the fringes of the forest of the Landes de Gascogne. The results of a survey are used to understand the way these urban fringes function : the representations of local inhabitants of the forest landscape and the recreational activities they practise in the forest as well as the consequences of this proximity on the way these landscape interfaces are shaped. Whereas the forest is not always among prevalent factors in initial residential choices, the discourse of the inhabitants relates to emotional aesthetic values which bear witness to the importance of certain uses and functions attributed to the forest, however artificial this landscape may be. These values are expressed via the appreciation of certain components of the forest landscape and through the development of the living environment in interfaces the shaping of which is more often the result of individual initiatives than that of community projects.